(3cJGH GdCQHYjf MOjkKG aj aVd GdLgGO hGdeLGgOjfs - (3YHO GdYXje Hf YHO Gdbhj Hf YHO Gddg, CHh eMeO, Rcj GdOjf GdefPQj ,J (B656 (3g` s ((3YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH Hf YHO GdSdGe s)
(3ChdgG (B:s
(3GdMeO ddg QGaY efGQ GdOjf hHYO abO QZH Edi HYV ef CQZH ai ELGHJg ef GdeQjOjf ai CMGOjK eMPhaI ai aVd GdLgGO hGdeLGgOjf s
(3BNQgG (B:s
(3GdMOjK GdSGHY hGdKdGKhf Yf cYH Hf eGdc QVi Gddg Yfg Cf QShd Gddg Udi Gddg Ydjg hSde bGd (B:" (3Cf CQhGMi GdTgOGA ai MO aWjhQ NVQ JYdb ef JeQ GdLfI Ch TLQ GdLfI (B" (3CNQLg GdJQePi hgh MOjK UMjM s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3HgG Jedc HGSe YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TjH Hf YHO GdSdGe hjQLY JGQjNgG Edi SfI (B1294 (3g`s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B30s
Keywords: (3GdeLGejYs